COMPARATIVE STUDY OF ZOOPLANKTON IN MAKHANA CULTIVATION POND AND PERENNIAL FISH POND IN DARBHANGA, NORTH BIHAR - NATH, ASHIM KUMAR; GUPTA, V. K.; KHAN, M. A.; PANDA, P. (Journal of the Inland Fisheries Society of India, 2021)
Darbhanga district of North Bihar, India lying between latitudes 26o 10¢ - 26o 17¢ N and longitudes 85o 54¢E - 85o 9¢, is traversed with fish and Makhana ponds. These water bodies can be profitably managed for cultivation of fish and Makhana (Euryale ferox), which are of high nutritive and medicinal value and fetch high price in National and International markets. Fishery in these ponds is a traditional practice without much intervention, excepting some stocking and harvesting. The present investigation was carried out on the zooplankton diversity, which is an important component of the food chain and fish yield to a great extent depends on their abundance. Makhana (Euryale ferox Salisb) plant, belonging to family Nymphaeaceae, is grown in ponds continuously for years. After harvesting of Makhana seeds from the bottom of ponds, the left over seeds serve as planting material for the next season. These Makhana growing ponds undergo gradual dereliction and get enriched with nutrients through anthropogenic and biotic sewers leading to eutrophication. Dehadrai (1994) opined that despite high organic nutrients in the pond soil due to the decay and decomposition of the Makhana plants, the plankton production remains sparse due to the shaded surface by the sprawling Makhana leaves during May to September. As a result, the metabolic gases remain in unfavorable proportions throughout the year making Makhana cultivated swamps completely unfavorable for cultivation of fish. Laal (1981) reported abiotic and biotic features of Makhana ponds and fish yield therein @ 200 kg ha-1yr-1. However, meager information is available on the relation between physico-chemical environment and dynamics of production respectively. Zooplankton production in the aquaculture in the paramonial fish pond has also been studied for comparison.